2003
DOI: 10.1002/jobm.200390018
|View full text |Cite
|
Sign up to set email alerts
|

Chromate tolerance caused by reduced hydroxyl radical production and decreased glutathione reductase activity in Schizosaccharomyces pombe

Abstract: The stable Cr(VI)-tolerant chr1-66T mutant of Schizosaccharomyces pombe, which carries one simple gene mutation responsible for Cr(VI) tolerance, accumulated and reduced the chromate anion (CrO(4)(2-)) significantly more slowly than did its parental strain 6chr(+). The mutant chr1-66T proved to be sensitive to oxidative stressors such as H(2)O(2), menadione, tert-butyl hydroperoxide and Cd(2+). Both the Cr(VI) tolerance and the oxidative stress sensitivity were attributed to a decreased specific glutathione re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Using such models, some metabolites and enzymes have been shown to be responsible for the modulation of yeast cell tolerance to chromate, e.g. glutathione and glutathione reductase [15][16][17], glucose-6-phosphate dehydrogenase [15], mitochondrial Mn-dependent superoxide dismutase [17], cytosolic Cu,Zn-superoxide dismutase and methionine sulfoxide reductase [18]. NADH-dependent chromate reductase was found in a chromate-resistant strain of Candida maltosa [19].…”
Section: Introductionmentioning
confidence: 99%
“…Using such models, some metabolites and enzymes have been shown to be responsible for the modulation of yeast cell tolerance to chromate, e.g. glutathione and glutathione reductase [15][16][17], glucose-6-phosphate dehydrogenase [15], mitochondrial Mn-dependent superoxide dismutase [17], cytosolic Cu,Zn-superoxide dismutase and methionine sulfoxide reductase [18]. NADH-dependent chromate reductase was found in a chromate-resistant strain of Candida maltosa [19].…”
Section: Introductionmentioning
confidence: 99%
“…Fe 2+ and Cu 2+ ) of strain RE007 [10]. As already suggested, this may be an atypical reaction because the addition of NADPH to the Cr(VI)-tolerant strain of S. pombe resulted in increased •OH production [9].…”
Section: Acta Biologica Hungarica 66 2015mentioning
confidence: 65%
“…The chr1-66T mutant was sensitive to oxidative stressgenerating agents such as H 2 O 2 , menadione, tert-butyl hydroperoxide and Cd 2+ . Both the Cr(VI) tolerance and the oxidative stress sensitivity were attributed to decreased specific GR and mitochondrial superoxide dismutase (Mn-SOD) activities [37]. As expected, the mutant cells were characterized by significantly decreased GSH and elevated intracellular superoxide concentrations [37].…”
Section: Mechanisms Of Chromium Sensitivity and Resistancementioning
confidence: 90%
“…Exposure to Cr(VI) also increases the level of the Hsp 104 chaperone protein in C. intermedia, elevates the intracellular level of the oxidized form of GSH, GSSG [107,108], regulates the yeast S. cerevisiae transcriptional activator MSN1 [109], and induces intracellular signal transduction processes [110]. This indicates that oxidative cell damage plays a pivotal role in cytotoxicity [37,111], but has left the crucial targets of ROS awaiting identification [112]. Sumner et al [112] concluded that the Cr-induced oxidative damage of proteins (oxidation of methionine moieties and carbonylation) had greater consequences on the cell physiology than the oxidation of other biomolecules (lipids and nucleic acids).…”
Section: Chromium Toxicity 41 Mechanisms Of Chromium Toxicitymentioning
confidence: 97%
See 1 more Smart Citation